Cover Jurnal Fitopatologi Vol. 17 No. 3, Mei 2021 - Sri Hendrastuti Hidayat (Jurnal Fitopatologi Indonesia, 2021)
This editorial contains the front cover, editorial page, and back cover of the Indonesian Journal of Phytopathology, JFI Vol. 17 No. 3, Mei 2021.